VARIABILITY OF MIXED LAYER DEPTH (MLD) AT MAKASSAR STRAIT - Wira Trihadi Geofary, Irvan
Indonesian Seas especially Makassar Strait has an unique bathymetry and also place where water mass from Pacific Ocean flows trough this strait to Indian Ocean and it is called ITF (Indonesian Throughflow). Mixed Layer Depth (MLD) which is the upper layer can be used to analyze for air-sea interaction processes. To determine the MLD we used the criterion temperature difference (?T=0.3OC) with 10 m of depth reference. The temperature profiles are collected from the observational data of ARLINDO mixing 1993 and 1994, INSTANT leg 3 cruise 2005, MITF cruise 2015. Due to the limited observational data, then we analyze the 20 years simulated data from Regional Ocean Model (ROMS) in 1995 - 2014 by Sofian (2015). MLD fluctuated every season, that deeper in winter season (December, January and February) with 34 meter depth. In March, April and May MLD become shallower to 25 meter. Summer season (June, July and August) at Makassar Strait cause MLD shallower to 24 meter, and shallowest point of MLD are in September, October and November with 22 meter depth. Monsoonal wind become a primary rule for mixing the mixed layer at in Southern area of this strait but not in Northern and Labani area. Fourier-Transform shows that the strongest signal for MLD is 6 months periods (seasonal) in Labani and Southern area and 3 years periods (interannual) in northern area. ENSO gives contribution to MLD during El Niño becomes shallower about 10 m and deeper about 10 m during La Niña compare with normal period with 2 months time lag.